Evaluation of the Effect of Coconut Coir Fiber Addition on Polypropylene Matrix Composite Properties - Milawarni, Milawarni; Yusniyanti, Erna; Nurlaili, Nurlaili; Suryati, Suryati (Politeknik Negeri Bengkalis, 2024)
Research has been conducted on coconut coir fiber composites with a polypropylene matrix. The aim of thisstudy is to examine the effect of adding coconut coir fiber to the polypropylene matrix on the physical and mechanicalproperties of the composite. The method used is the hand lay-up method, which is carried out in the laboratory by initiallypreparing coconut coir fibers and polypropylene matrix, then mixing them and placing them into molds. Subsequently, hotpressing is performed at a pressure of 38 atm and a temperature of 150°C for 30 minutes. After being cooled to roomtemperature, the composite is tested according to testing standards. The results obtained are the density values of thecoconut coir fiber (CCF) and polypropylene (PP) composites ranging from 0.543-0.7 g/cm3, water absorption capacityranging from 0.5-16.45%, moisture content ranging from 0.14 – 0.22%, and thickness swelling value ranging from 0.76 -15%. For mechanical properties, the MOR value ranges from 11.22 – 19.20 MPa and the MOE value ranges from 220 –350 MPa.